THE USE OF ANIMATED VIDEO AS A MEDIA TO ENHANCE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT - Anggraini, Lulu Hasna (RETAIN, 2021)
Learning English in schools is improving students' understanding of English and applying it in daily life. One of the activities taught in English is narrative text. Narrative texts are usually very long and often make students bored and lazy to learn them. This study is based on the students’ needs who feel bored during reading narrative text in English. Students need a tool that can help them comprehend the story and answer the questions given. The animated video is the answer to this problem. The objectives of this study were to investigate the implementation of animated video as a medium to enhance students’ reading comprehension in narrative text, to use the animated video to enhancing students’ reading comprehension in narrative text, and to know students’ perceptions about the implementation of this medium in learning narrative text. A qualitative approach was used in this study by collecting data from observation and interviews at X MIA 5 MAN Sidoarjo. This study reported that using animated video to enhance students’ reading comprehension in narrative text played a positive role because it could make it easier for them to find the story's content and help them answer reading comprehension questions. They also really like the medium because it allows them to describe the chronological events in the story. Therefore, animated video is a suitable medium to enhance students’ reading comprehension in narrative text. Keywords: animated video, reading comprehension, narrative text.